Exploring action coils for bystander intervention: Modeling bystander consequences. Issue 3 (3rd April 2021) - Banyard, Victoria; Moschella, Elizabeth; Jouriles, Ernest; Grych, John
Abstract: Objective: Individuals who take action to reduce sexual assault can experience a range of positive and negative consequences as a result of helping. This study examined how different types of consequences explain variation in confidence and intent to help. Participants: Nine hundred sixty-six individuals who reported intervening in a situation involving interpersonal violence; approximately half were recruited from university psychology courses and half through Amazon's Mechanical Turk. Data were collected from September to December of 2016. Methods: Participants completed measures of consequences related to helping, bystander efficacy, and intent to help. Results: Positive reactions from victims and other individuals who witnessed the situation were related to higher efficacy and intent, while negative reactions were associated with lower efficacy and intent. Actionists' personal feelings (ie, positive and negative) about their behavior mediated these relationships. Conclusions: Bystander training on campuses should address the range of potential consequences actionists face.